Stress, burnout, coping em padres responsáveis pela formação de seminaristas católicos - Morais, Maria de Fátima Alves de (2008)
This research has its main objetive do verify if and how the stress and the burnout phenomena are present in catholic priests who are in charge of the formation of the catholic clergy in Brazil. It tries to describe in a positive way the stressors that are characteristics of the tension situations of this special group. At the same time it aims to find out what are the strategies used by this group in order to cope with the problems they find in their everyday activity as priests and formators. The research is based in three very well known and used instruments which are adequately adapted for the group under investigation: the IBM of C. Maslach, the Inventory of Coping Strategies of Lazarus and Folkman and the Inventory of Stresses (ISSL) of the brazilian researcher M. Lipp. The two firt instruments wer submitted to a factor analysis and different statistical comparisons between the results were made and analysed. Besides that the researcher created a special Questionnaire in order to find out what are the really causes of stress in concrete situation of the houses of formation. In the first chapter the author presents the theoretical aspects of the question under discussion; in chapter two the results of the factorial analysis and of the correlations founded are presented; in the last chapter the autor comments and analyses those results. In the conclusion the strategies for coping with the difficulties indicated by the formators are listed